A review on the cleavage priming of the spike protein on coronavirus by angiotensin-converting enzyme-2 and furin - Hasan, Anwarul (J Biomol Struct Dyn, 2020)
The widespread antigenic changes lead to the emergence of a new type of coronavirus (CoV) called as severe acute respiratory syndrome (SARS)-CoV-2 that is immunologically different from the previous circulating species. Angiotensin-converting enzyme-2 (ACE-2) is one of the most important receptors on the cell membrane of the host cells (HCs) which its interaction with spike protein (SP) with a furin-cleavage site results in the SARS-CoV-2 invasion. Hence, in this review, we presented an overview on the interaction of ACE-2 and furin with SP. As several kinds of CoVs, from various genera, have at their S1/S2 binding site a preserved site, we further surveyed the role of furin cleavage site (FCS) on the life cycle of the CoV. Furthermore, we discussed that the small molecular inhibitors can limit the interaction of ACE-2 and furin with SP and can be used as potential therapeutic platforms to combat the spreading CoV epidemic. Finally, some ongoing challenges and future prospects for the development of potential drugs to promote targeting specific activities of the CoV were reviewed. In conclusion, this review may pave the way for providing useful information about different compounds involved in improving the effectiveness of CoV vaccine or drugs with minimum toxicity against human health. Communicated by Ramaswamy H. Sarma